2008
DOI: 10.2319/120706-495.1
|View full text |Cite
|
Sign up to set email alerts
|

Autotransplantation of 28 Premolar Donor Teeth in 24 Orthodontic Patients

Abstract: Objective: To test the null hypothesis that premolar autotransplantation is not successful for orthodontic patients. Materials and Methods: In the present study, 28 premolar transplants from 24 orthodontic patients were associated with orthodontic treatment. At a routine 3-month appointment, patients underwent a dental radiograph and a chair-side observation for periodontal problems. Three sets of dental radiographs were taken by one dental assistant using a custom holder at: preoperation (T0), 2 year postoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(87 citation statements)
references
References 28 publications
2
82
2
1
Order By: Relevance
“…The success rate of transplanted teeth in this study, 58.1%, is lower than the success rate of transplantation reported in other studies (~90%) [37,[40][41][42]. This can be explained by the fact that most studies included all tooth types in their calculation of the success rate of the transplantation procedure.…”
Section: Discussioncontrasting
confidence: 53%
“…The success rate of transplanted teeth in this study, 58.1%, is lower than the success rate of transplantation reported in other studies (~90%) [37,[40][41][42]. This can be explained by the fact that most studies included all tooth types in their calculation of the success rate of the transplantation procedure.…”
Section: Discussioncontrasting
confidence: 53%
“…5 Another study of 28 transplanted premolars in 24 patients reported 100% success 4 to 14 years posttreatment. 30 Lundberg and Isaksson 12 recom-mended that immature donor teeth should be placed in infraocclusion and mature donor teeth in occlusion or slight infraocclusion: this recommendation was followed in the present study. In a study of 80 patients by Josefsson et al 31 using the same success criteria as in the present study, 110 teeth were transplanted to the lower second premolar site.…”
Section: Discussionmentioning
confidence: 99%
“…[19] Auto-transplantation has been used to replace missing teeth and teeth of poor prognosis. [20][21][22][23][24][25][26] Auto-transplantation of teeth and orthodontic space closure constitute feasible biological approaches for substitution of incisors because of the permanence of the result, particularly in growing individuals.…”
Section: Auto-transplantation and Orthodontic Closurementioning
confidence: 99%